THE INFLUENCE OF THIRD PARTY DEPOSITS TOWARDS THE INCOME OF COMMERCIAL BANKS IN INDONESIA - Dian Kurnianingrum, Riana Enny Widayanti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Third party deposits accumulated by banks can be utilized for non-earning assets, which do not necessarily result in maximizing the bank’s income. Therefore, researchers are interested in analyzing the relationship between third party deposits and the income of banks. This research analyzes the relationship of third party deposits and the income of banks under three bank categories, namely: state-owned bank, foreign exchange commercial banks, and all commercial banks in Indonesia. The data used in this research are time series data from 2008 until 2014, The data were analyzed using the t-test and the Pearson correlation and linear regression. From the research results, it can be concluded that third party deposits influence the banks’ income and the correlation between the variables is positive. This means that an increase in third party deposits will lead to an increase in income, and vice versa.